Disability Pensions in the European Union - Wiener, Mitchell (World Bank, Washington, DC, 2020)
Disability is a complex, evolving and multidimensional concept. According to the World Disability report (2011), disability will be an even greater concern as its prevalence is on the rise due to Ageing Populations as well as the Global increase in chronic health conditions such as diabetes, cardiovascular disease, cancer and mental health disorders. In this paper, the authors look at the basic design features and fiscal costs of the sick pay, sick leave and disability pensions program in each of the Member States of the European Union. As will be seen, it is difficult to draw any policy conclusions or find much in the way of trends in the data. Nevertheless, the authors highlight the heterogeneity in practices across various countries through our analysis, suggest areas for additional analysis or research, and provide suggestions for strengthening disability pension systems in the future. The authors also include case studies for two countries (The Netherlands and Poland) to illustrate the characteristics of recent reforms and lessons learned. For most purposes, in this paper, disability benefits refer to a combination of sick pay, sick leave and disability pensions payable from social insurance programs. This paper is arranged as follows: (ii) Section II of this report discusses the social, financial, and demographic arguments for countries to focus increased attention now on the design, administration and financing of their sick pay, sick leave and disability pension programs; (iii) Section III discusses the basic terminology and issues in disability pensions; and (iv) Section IV reviews the current practices of the EU countries in the areas of disability covered by the report.